Teaching Techniques Used By Tutor In English Tutorial Program At Muhammadiyah University Of Surakarta - Prasetya, Ega, MAULY HALWAT HIKMAT, Ph.D (2016)
This research aims at identifying techniques are used by tutor, the purpose of the techniques used and tutor's roles in teaching learning process in English Tutorial Program (ETP) UMS. This research is descriptive research. The subjects of this research are students of Class DD of FEB UMS. The object of the study is teaching techniques used by tutors in English Tutorial Program (ETP) UMS. Method used to collect the credible data in this research is interview, observation, and documentation. Then, the data analyzed used Miles and Huberman model, which are reducing data, data display and verification of the data.The result shows that tutors used several techniques in teaching learning process. The techniques used are lecturing, role play and giving assignment. Different techniques show different purposes of the expected achievement. Lecturing is used to make students easier in understanding the material they've never know. Role play is used to make students experience what they have learned by themselves. Tutor's roles in teaching learning process based on the techniques used are as controller, commentator, instructor, consultant and assessor. Keywords: Techniques, English Tutorial Program (ETP), purpose, roles